2022
DOI: 10.24180/ijaws.1098482
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Genetic Diversity in Banana and Bell Pepper Lines Using Molecular Markers

Abstract: Successful hybrid cultivar breeding is depend on the high genetic diversity of the plant sources, as well as the homozygous and genetically distant lines requiring hybridization. The aim of this study is to determine the genetic distance between the inbred lines of pepper (Capsicum annuum L.) in order to increase efficacy of the breeding program. In this study, the genetic distances between the inbred lines of 44 bell peppers and 35 banana peppers were investigated using the SRAP (Sequence Related Amplified Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, the polymorphism rate of the primers was lower (60.77%) than our results. In another study using SRAP primer combinations for the molecular characterization of different pepper genotypes (Nas and İlbi 2022), it was reported that the number of polymorphic bands per primer combination ranged from 1 to 6. Zhong et al (2021) reported that SSR makers revealed average PIC, MAF, NE, I, and H values were 0.29, 0.755, 1.705, 0.576, and 0.331 in C. frutescens, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the polymorphism rate of the primers was lower (60.77%) than our results. In another study using SRAP primer combinations for the molecular characterization of different pepper genotypes (Nas and İlbi 2022), it was reported that the number of polymorphic bands per primer combination ranged from 1 to 6. Zhong et al (2021) reported that SSR makers revealed average PIC, MAF, NE, I, and H values were 0.29, 0.755, 1.705, 0.576, and 0.331 in C. frutescens, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The results of PCA can lead to a better understanding of genetic diversity and structure of the pepper populations using that SRAP primers. Nas and İlbi (2022) reported that the first component in the PCA applied to the data obtained with SRAP markers explained 69.91% and 70.49% of the variation for banana pepper and bell pepper lines, respectively. In another study, the first PC axis explained 65% of the total variance as determined by PCA results obtained from SRAP marker data in the diversity of Turkish pepper genotypes (Bozokalfa et al 2017).…”
Section: Discussionmentioning
confidence: 99%